cDNA cloning and transcription level of 1-deoxy-D-xylulose 5-phosphate reductoisomerase (dxr) gene in Croton stellatopilosus - Juraithip Wungsintaweekul (Prince of Songkla University, 2012)
Prince of Songkla University